Effect of Social Support on the Psychological Adjustment of Chinese Left-Behind Rural Children: A Moderated Mediation Model - Fan, Zhiyu; Fan, Xinghua (Frontiers in Psychology, 2021)
There are tens of millions of children left behind by one or both rural-to-urban migrant parents (left-behind children, LBC) in rural China. Compared to non-left-behind children (NLBC), LBC are disadvantaged in psychological adjustment. Research has shown social support can help LBC grow up healthily, but the plausible mechanisms linking support to adjustment remain unclear. The present study investigated the mediating role of basic psychological need satisfaction (BPNS) in the above relationship, as well as whether the predictive pathways of support on adjustment and BPNS were moderated by resilience in a sample of 692 LBC and 264 NLBC. Structural equation modeling indicated social support positively predicted LBC's psychological adjustment, which was completely mediated by BPNS. In addition, the mediating effect was weaker for LBC with higher levels of resilience, which indicated resilience was a necessary asset for LBC's growth amid the adversity of low social support.